El Caribe como espejo y descentramiento en la poética de Derek Walcott - Claisso, Claudia (2019)
The work analyzes the integration and projection of the Caribbean that Derek Walcott constructed through analogical bridges and the translation of the imaginary of the book-archive to the landscape in The Antilles, fragments of an epic memory (1992). On the other hand, it stops at the evaluation that the author of Omeros (1990) made of imitation as a decisive intercultural matrix in The Caribbean. Culture or mimicry? (1974). It emphasizes theoretical positions constructed in the essay based on the questioning of hypotheses proposed by Vidia Naipaul in The Mimic Men (1967) and considers the relevance achieved by the manifestations of the specular relationship in the region anthropological life. Finally it describes the intertextual articulation that exists between that process and the representations drawn in Aimé Césaire´s Cahier d´un retour au pays natal (1939) by means of which the belief in the cultural originality and the Eurocentrism are questioned.